Channel Availability for Mobile Cognitive Radio Networks - Cacciapuoti, Angela Sara (Elsevier, 2015)
Channel availability is defined as the probability of a licensed channel being available for the communications of unlicensed users. Channel availability is a key parameter for an effective design of channel selection strategies as well as routing metrics in cognitive radio networks. In static scenarios, the availability of a channel depends only on the primary user’s activity. Differently, in mobile scenarios, the availability of a channel dynamically varies in time due to the changes of the users’ relative positions. In this paper, we design a channel-availability estimation strategy by explicitly accounting for the features of mobile scenarios. The simulation results reveal the benefits of adopting the proposed strategy in cognitive radio networks.